Roles of Bromodomain Extra Terminal Proteins in Metabolic Signaling and Diseases - Dayu Wu; Qiong Duan (MDPI AG, 2022)
BET proteins, which recognize and bind to acetylated histones, play a key role in transcriptional regulation. The development of chemical BET inhibitors in 2010 greatly facilitated the study of these proteins. BETs play crucial roles in cancer, inflammation, heart failure, and fibrosis. In particular, BETs may be involved in regulating metabolic processes, such as adipogenesis and metaflammation, which are under tight transcriptional regulation. In addition, acetyl-CoA links energy metabolism with epigenetic modification through lysine acetylation, which creates docking sites for BET. Given this, it is possible that the ambient energy status may dictate metabolic gene transcription via a BET-dependent mechanism. Indeed, recent studies have reported that various BET proteins are involved in both metabolic signaling regulation and disease. Here, we discuss some of the most recent information on BET proteins and their regulation of the metabolism in both cellular and animal models. Further, we summarize data from some randomized clinical trials evaluating BET inhibitors for the treatment of metabolic diseases.